2021
DOI: 10.3390/pathogens10060667
|View full text |Cite
|
Sign up to set email alerts
|

Search for Promising Strains of Probiotic Microbiota Isolated from Different Biotopes of Healthy Cats for Use in the Control of Surgical Infections

Abstract: Despite the introduction of modern methods of treatment, the creation of new generations of antibacterial agents, and the constant improvement of aseptic and antiseptic methods, the treatment of purulent–inflammatory processes remains one of the most complex and urgent problems in veterinary practice. The article presents the results of the isolation of indigenous microbiota from various biotopes of healthy cats, as well as the study of their biological marker properties for the selection of the most optimal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 43 publications
0
28
0
10
Order By: Relevance
“…Infectious diseases can produce complications due to the formation of microbial biofilms in the body. Many chronic fungal and bacterial diseases are associated with biofilms, since the biofilms adhere strongly to the cells of the human or animal body, and are less susceptible to antibiotic therapy than individual cells [ 16 - 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Infectious diseases can produce complications due to the formation of microbial biofilms in the body. Many chronic fungal and bacterial diseases are associated with biofilms, since the biofilms adhere strongly to the cells of the human or animal body, and are less susceptible to antibiotic therapy than individual cells [ 16 - 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…A number of recent studies have revealed the features of the intestinal microbiome in cats in normal conditions, as well as in various pathological conditions [11,14,18,33]. However, these studies did not analyze the fecal gut microbiota in cats with dysbiosis of varying severity.…”
Section: Discussionmentioning
confidence: 99%
“…A number of undeniable advantages are inherent in small animals: they improve our mood, reduce emotional and physical stress, help their owners cope with depression, create a feeling of exaltation, as well as a warm and cozy atmosphere in the hearth. In addition, dogs and cats contribute to the psychological development of children with autism, cerebral palsy, and developmental delays and improve the quality of life for lonely, elderly people and patients with cardiovascular pathologies [8][9][10][11]. However, despite the rapid development of veterinary medicine, many issues of diseases in small domestic animals, which are caused by associations of opportunistic and saprophytic microbiota, as well as the improvement of diagnostic approaches, prevention, and therapy, remain poorly understood [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations